2018
DOI: 10.1101/gad.307330.117
|View full text |Cite
|
Sign up to set email alerts
|

An inactivating mutation in the histone deacetylase SIRT6 causes human perinatal lethality

Abstract: It has been well established that histone and DNA modifications are critical to maintaining the equilibrium between pluripotency and differentiation during early embryogenesis. Mutations in key regulators of DNA methylation have shown that the balance between gene regulation and function is critical during neural development in early years of life. However, there have been no identified cases linking epigenetic regulators to aberrant human development and fetal demise. Here, we demonstrate that a homozygous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 65 publications
2
38
0
Order By: Relevance
“…Previous studies have identified loss-of-function mutations of a neighboring aspartate to either tyrosine or histidine (D63Y/H). SIRT6 D63Y was selected for in naturally occurring human tumors, and D63H was identified as a driving mutation in four consecutive late fetal losses of a consanguineous couple (11,36). These studies and our analysis suggest that SIRT6 catalysis is particularly sensitive to mutation of the NAD ϩ -binding loop.…”
Section: Editors' Pick: Mechanism Of Sirt6 Activationmentioning
confidence: 67%
“…Previous studies have identified loss-of-function mutations of a neighboring aspartate to either tyrosine or histidine (D63Y/H). SIRT6 D63Y was selected for in naturally occurring human tumors, and D63H was identified as a driving mutation in four consecutive late fetal losses of a consanguineous couple (11,36). These studies and our analysis suggest that SIRT6 catalysis is particularly sensitive to mutation of the NAD ϩ -binding loop.…”
Section: Editors' Pick: Mechanism Of Sirt6 Activationmentioning
confidence: 67%
“…Deletion of SIRT6 in cynomolgus monkey leads to hyperacetylation of histone, activating the long noncoding RNA H19 and resulting in prenatal developmental retardation and neonatal death [60]. A homozygous SIRT6 inactive mutation in human also leads to hyperacetylation of H3K9 and H3K56, dramatically elevating pluripotent genes and causing severe congenital anomalies and perinatal lethality [61].…”
Section: Sirt6 Epigenetically Promotes Proper Lineage Commitment Of Ementioning
confidence: 99%
“…The only mutant that showed no effect on binding was D63Y, where the amino acid did not impair the charge as strongly as the D63H. Interestingly, mutations in D63 were previously reported to provoke the loss of SIRT6 function in cancer, and have been recently shown to be lethal in humans (Ferrer et al, 2018) .…”
Section: Sirt6 Binds Dna Ends As a Dimermentioning
confidence: 98%